Spray drying and storage of probiotic‐enriched almond milk: probiotic survival and physicochemical properties. (25th April 2020) - Lipan, Leontina; Rusu, Bogdan; Sendra, Esther; Hernández, Francisca; Vázquez‐Araújo, Laura; Vodnar, Dan Cristian; Carbonell‐Barrachina, Ángel A
Abstract: BACKGROUND: The combination of the nutritional profile of almond milk with the benefits of probiotic bacteria is an interesting development to meet the demand for sustainable and health‐promoting food. Almond milk inoculated with probiotic Lactobacillus plantarum (ATCC8014) was spray dried and the almond, its milk, and powders were characterized physicochemically. Samples were characterized in terms of bacterial survival before and after atomization. Bacterial viability and total fatty acid changes were studied during 8 months' storage at 4 and 22 °C. RESULTS: Results showed adequate physicochemical properties and an optimal bacterial survival rate, maintaining almost the same values before and after the spray‐drying operation. A decrease was observed in the cell viability for samples stored at 4 °C. However, the cell count was maintained above the minimum level suggested (10 7 living cells) to allow potential probiotic functionality for 8 months. On the other hand, the count cell of powders stored at 22 °C was below the minimum level required after 6 months. The fatty acids profile was not significantly ( P > 0.05) affected by storage time and temperature. CONCLUSION: A new almond‐based‐product with probiotics was developed to meet consumer demands. Almond nutrients were recovered from almond milk powder and were found to be a good source of K and high in Mg and in monounsaturated fat. The viability of bacteria was assured during 8 months of storage at 4 °C and up to 6 months for samples stored at 22 °C. © 2020 Society of Chemical Industry